2021
DOI: 10.17159/2078-5151/2021/v59n3a3264
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and lower extremity amputation -rehabilitation pathways and outcomes at a regional hospital

Abstract: BACKGROUND: Lower extremity amputations (LEAs) are most frequently due to diabetes mellitus (DM), a disease on the rise. The objective of this study was to determine the prevalence and aetiology of LEAs at Addington Hospital from 2013 to 2017 and to explore the physiotherapy referral practices and outcomes METHODS: Retrospective study carried out at Addington Hospital, Durban. Patients who underwent LEAs were filtered from theatre registers and the hospital Meditech database. Data collected included patients' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…This variable considered total diet score (=17), total exercise score (=17), total medication score (=12), total testing score (=12), footcare (=7), smoking (=1), alcohol (=1), doctor (=5), and self-care (=5), giving a total self-management score = 77. Assessed self-management was categorised as poor (0-37), fair (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57), and good (58-77).…”
Section: Sociodemographic Data and Diabetes Measures Activities And K...mentioning
confidence: 99%
See 2 more Smart Citations
“…This variable considered total diet score (=17), total exercise score (=17), total medication score (=12), total testing score (=12), footcare (=7), smoking (=1), alcohol (=1), doctor (=5), and self-care (=5), giving a total self-management score = 77. Assessed self-management was categorised as poor (0-37), fair (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57), and good (58-77).…”
Section: Sociodemographic Data and Diabetes Measures Activities And K...mentioning
confidence: 99%
“…In Table 4, the combined scores of self-management activities and compliance were assessed over the last eight weeks using DSMQ. The assessed self-care management activities are presented as means ± SD, frequencies, and proportions, and categorised as poor (0-37), fair (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57), and good (58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77). The results showed that only 10% had a good total diet, 10% were good with exercise, 75% had a good total medication score, and only 3% had a good total self-testing score.…”
Section: Self-care Management Activities Of the Patientsmentioning
confidence: 99%
See 1 more Smart Citation